Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1359/jbmr.081230
|View full text |Cite
|
Sign up to set email alerts
|

miR-196a Regulates Proliferation and Osteogenic Differentiation in Mesenchymal Stem Cells Derived From Human Adipose Tissue

Abstract: The elucidation of the molecular mechanisms that govern the differentiation and proliferation of human adipose tissue-derived mesenchymal stem cells (hASCs) could improve hASC-based cell therapy. In this study, we examined the roles of microRNA (miRNA)-196a on hASC proliferation and osteogenic differentiation. Lentiviral overexpression of miR-196a decreased hASC proliferation and enhanced osteogenic differentiation, without affecting adipogenic differentiation. Overexpression of miR-196a decreased the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
142
5
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 34 publications
2
142
5
3
Order By: Relevance
“…40 In addition, overexpression of miR-196a inhibited the proliferation of human adipose tissue-derived mesenchymal stem cells while enhancing osteogenic differentiation. 41 Our results show that NPC cells become radioresistant by reducing the expression of miR--196a, and expression of miR-196a restores the sensitivity of radioresistant NPC to radiation therapy. Importantly, the expression level of miR-196a in clinical NPC samples is correlated with the sensitivity of NPC to radiotherapy.…”
Section: Discussionmentioning
confidence: 53%
“…40 In addition, overexpression of miR-196a inhibited the proliferation of human adipose tissue-derived mesenchymal stem cells while enhancing osteogenic differentiation. 41 Our results show that NPC cells become radioresistant by reducing the expression of miR--196a, and expression of miR-196a restores the sensitivity of radioresistant NPC to radiation therapy. Importantly, the expression level of miR-196a in clinical NPC samples is correlated with the sensitivity of NPC to radiotherapy.…”
Section: Discussionmentioning
confidence: 53%
“…For example, the misexpression of miR-196a in the anterior of Xenopus laevis embryos caused eye anomalies (Qiu et al, 2009). Moreover, Kim et al (2009) showed that miR-196a was an important regulator for the proliferation and osteogenic differentiation of human adipose tissuederived mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Runx2 has been shown to negatively regulate expression of the miR cluster 23a∼27a∼24-2, thereby increasing expression of bone markers and enhancing osteoblast differentiation (14). In human adipose tissue-derived MSCs (hADSCs), miR-26a has been reported to repress the translation of the osteogenic marker, SMAD1 (15), whereas overexpression of miR-196a regulates HOXC8, enhances osteogenic differentiation, and decreases hADSC proliferation (16). miR-125b has been shown to inhibit osteoblast differentiation in the mouse MSC line ST2 (17), whereas miR-133 and -135 directly target Runx2 and Smad5, respectively, and inhibit differentiation of osteoprogenitors of C2C12 mesenchymal cells (18).…”
mentioning
confidence: 99%